Relevant factors in research activity of ukrainian social workers: postmodern studies - Povidaichyk, Oksana; Lisovets, Oleg; Bilyk, Olena; Onypchenko, Oksana; Hrynyk, Ihor; Kulava, Kateryna (My University, 2022)
The article deals with theoretical, practical, partly - historical aspects of scientific research of modern Ukrainian and foreign sociologists and social workers. The aim of the research is to analyze and summarize the following three key aspects: a) historical destructive moments in the development of Ukrainian/Soviet sociology; b) the orientation of the vector of postmodernist research of foreign scholars who had no censorship restrictions on their works; c) the main problematics of current Ukrainian sociological research. The latter, despite their deep materialistic tradition, find opportunities for new non-empirical approaches. In the article with the help of analysis of methodical sources, generalization of their content and presentation and interpretation of individual statistical data the authors substantiate: socio-economic, managerial and pedagogical reasons can systematically present the problematics of the current research of social workers. However, the postmodern aspect, still not "reworked" by the Ukrainian society, has not yet left its final mark on the social research. The international significance of the article lies in the interest of countries of transitional democracies and economies, previously under totalitarian influence, to acquire full emancipation and neo-liberalization concerning social problems and humane ways of solving them
Relevant factors in research activity of ukrainian social workers: postmodern studies / O. Povidaichyk, O. Lisovets, O. Bilyk, O. Onypchenko, I. Hrynyk, K. Kulava // Postmodern Openings, 2022. – № 13 (4). – Р. 561-578
Keywords: social work; research activity; social support strategies; technologies; groups of factors; socio-economic transformations